PENGETAHUAN DAN SIKAP WUS TENTANG DETEKSI DINI KANKER LEHER RAHIM DI WILAYAH KERJA PUSKESMAS DATUK BANDAR TAHUN 2018 - MELISA JUNI HASIBUAN; ROSTINA AFRIDA POHAN (JURNAL ILMIAH KOHESI, 2019)
Cervical cancer called cervical cancer or cervical cancer is a disease that attacks the mouth or cervix. This section is the lower part of the uterus that is protruding or indented into the vaginal cavity. Individual factors and lifestyle is the trigger for cervical cancer.This study was a descriptive study that aims to see the WUS Knowledge and Attitude Eligible for Early Detection of Cervical Cancer. This study used a questionnaire as a data collection tool, the sample used in this study as many 32 people.Results of research on knowledge shows that of the 32 respondents who researched the majority of respondents have moderate knowledge that as many as 19 people (59.4%), and the minority has a low knowledge of as many as five people (15.6%). While the results of research on attitudes indicates the majority of respondents have a good attitude as many as 19 people (59.4%), and the minority has a lack of as many as four people (12.5%).